ANATOMÍA MACROSCÓPICA, IRRIGACIÓN Y DRENAJE VENOSO DEL APARATO REPRODUCTOR FEMENINO DE LA LLAMA (Lama glama). - León M., Eric (2011)
The anatomical description of the reproductive tract of the female llama was studied in four animals. Macroscopically, the reproductive system is morphologically similar to the cow. However, the difference is the absence of intercornual ligament and cotyledons, and the presence of an intercornual septum, as in the alpaca. The distribution of the arteries and veins that irrigated and drained the blood to and from the pelvic cavity and reproductive system presented a vascular distribution almost equal to the ruminant’s pattern and then, they followed a pattern similar to that on the equine. At the reproductive system level, blood vessels adopted a totally different pattern from those described for domestic species. Some arteries had never been described such as the caudal vaginal artery, medium vesical artery, cranial vaginal artery, dorsal uterine artery with its lateral and medial branches, and the arch cervical artery. Each artery had the corresponding satellite vein. The left uterine horn presented a better irrigation as the right uterine artery send its medial right branch to the left side of the reproductive system; moreover, the arch cervical artery established communication between the left and right uterine arteries through the cervix ventral surface. This artery could emerge from the uterine artery itself as well as from its medial branch.